1999
DOI: 10.1046/j.1365-2036.1999.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, placebo‐controlled comparison of rabeprazole 20 mg vs. omeprazole 20 mg in the treatment of erosive or ulcerative gastro‐oesophageal reflux disease

Abstract: Background: Rabeprazole sodium is the most recent member of a class of substituted benzimidazole molecules known as proton pump inhibitors. Other proton pump inhibitors have been shown to be effective in healing oesophagitis. Methods: In this randomised, double‐blind, multicentre study, conducted at 27 European sites, the efficacy and safety of rabeprazole and omeprazole were compared in patients with erosive or ulcerative gastro‐oesophageal reflux disease (GERD).100 patients received rabeprazole 20 mg, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 19 publications
7
102
1
5
Order By: Relevance
“…22 This is in accordance of our study, which shows good effect in 82.86% patients. 21 Data of our study lie close to this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…22 This is in accordance of our study, which shows good effect in 82.86% patients. 21 Data of our study lie close to this study.…”
Section: Discussionsupporting
confidence: 58%
“…8 According to a study, rabeprazole provided relief in about 73% of patients after 8 weeks treatment. 21 When rabeprazole alone provided relief in 73% patients and 57-79% patients got benefi ted by itopride alone, it might be assumed that their combination will provide more benefi t than each alone. Similarly, our study shows a benefi t in 91.43% patients.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 summarizes the comparison of efficacy of rabeprazole vs. the other proton pump inhibitors. In two studies measuring the healing of oesophagitis, rabeprazole 20 mg was similar to omeprazole 20 mg. 6,7 There were no data comparing oesophagitis healing and/or GERD symptom relief with lower doses of rabeprazole vs. standard doses of any proton pump inhibitor. A single study indicated that low-dose rabeprazole (10 mg) was similar to standard-dose rabeprazole (20 mg) and standard-dose omeprazole (20 mg) in the maintenance of healing of oesophagitis.…”
Section: Resultsmentioning
confidence: 99%
“…Dekkers et al showed that, at 8 weeks, 38% of patients have complete resolution of their symptoms, whereas 73% have significant improvement from baseline. 11 In the current study, outcome assessments by patients themselves were categorized as satisfied versus dissatisfied. Agreement between physician and patient regarding their assessment of symptomatic GERD can be poor.…”
Section: Measurement Of Treatment Effectmentioning
confidence: 99%